2012
DOI: 10.1105/tpc.112.097022
|View full text |Cite
|
Sign up to set email alerts
|

Transposase-Derived Proteins FHY3/FAR1 Interact with PHYTOCHROME-INTERACTING FACTOR1 to Regulate Chlorophyll Biosynthesis by Modulating HEMB1 during Deetiolation in Arabidopsis

Abstract: Successful chlorophyll biosynthesis during initial light exposure is critical for plant survival and growth, as excess accumulation of chlorophyll precursors in darkness can cause photooxidative damage to cells. Therefore, efficient mechanisms have evolved to precisely regulate chlorophyll biosynthesis in plants. Here, we identify FAR-RED ELONGATED HYPOCOTYL3 (FHY3) and FAR-RED IMPAIRED RESPONSE1 (FAR1), two transposase-derived transcription factors, as positive regulators of chlorophyll biosynthesis in Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(168 citation statements)
references
References 77 publications
(126 reference statements)
8
154
0
Order By: Relevance
“…We show that the first 5 min of exposure to relatively high levels of light (60 µmol m 22 s 21 ) are critical for the survival of etiolated seedlings and that PIF1, PIF3, and possibly also PIF5 are required for survival during the onset of illumination (Figure 1). In addition, the survival rate of plants exposed to light correlates inversely with the levels of Pchlide, in agreement with our previous report (Tang et al, 2012). Pchlide is a potent photosensitizer in the chloroplast that leads to photooxidative damage in plants (op den Camp et al, 2003).…”
Section: Discussion Key Light Signaling Components Regulate Singlet Osupporting
confidence: 78%
See 4 more Smart Citations
“…We show that the first 5 min of exposure to relatively high levels of light (60 µmol m 22 s 21 ) are critical for the survival of etiolated seedlings and that PIF1, PIF3, and possibly also PIF5 are required for survival during the onset of illumination (Figure 1). In addition, the survival rate of plants exposed to light correlates inversely with the levels of Pchlide, in agreement with our previous report (Tang et al, 2012). Pchlide is a potent photosensitizer in the chloroplast that leads to photooxidative damage in plants (op den Camp et al, 2003).…”
Section: Discussion Key Light Signaling Components Regulate Singlet Osupporting
confidence: 78%
“…Other transcription repressors or activators might also be involved in this process by interacting with PIFs and HY5 proteins. We recently found that FAR-RED ELONGATED HYPOCOTYL3 (FHY3) and FAR-RED-IMPAIRED RESPONSE1 (FAR1) participate in regulating Pchlide synthesis and seedling greening by interacting and cooperating with PIF1 (Tang et al, 2012). HY5 feedback regulates phyA signaling homeostasis by interacting with FHY3 and FAR1 (Li et al, 2010).…”
Section: Interaction Between Bzip and Bhlh Transcription Factorsmentioning
confidence: 99%
See 3 more Smart Citations